Public Finance and Economic Development : Reflections Based on the Experience in China - Gordon, Roger H. (World Bank, Washington, DC, 2017)
Low tax revenue and slow economic growth are two central concerns in developing countries. However, policies that raise tax revenue also harm economic growth. With tax revenue coming mainly from large capital-intensive firms, and with a large informal sector, policies that aid large firms and policies that discourage entry of new firms both help increase tax revenue. Entrepreneurial activity as a result is discouraged, lowering growth. There is a basic tension in policy design between current tax revenue and economic growth. In fact, a loss in tax revenue can itself reduce growth, due to less spending on education and infrastructure. It can also undermine political support for the reforms from the poor and from government bureaucrats, both of whom are key beneficiaries of government expenditures. What policies encourage growth without undue loss of current expenditures? One is debt finance, but this creates the risk of a financial crisis if tax revenue rises too slowly to repay this debt. A second is user fees, but such fees still undermine political support from the poor. A third is partial reform, maintaining both higher taxes on and some protection for easily taxed firms, even while barriers to entry are eased.